A zoogeographical boundary between the Palaearctic and Sino‐Japanese realms documented by consistent north/south phylogeographical divergences in three woodland birds in eastern China. (20th April 2016) - Song, Gang; Zhang, Ruiying; Qu, Yanhua; Wang, Zhiheng; Dong, Lu; Kristin, Anton; Alström, Per; Ericson, Per G. P.; Lambert, David M.; Fjeldså, Jon; Lei, Fumin
Abstract: Aim: The location of zoogeographical boundaries in eastern China has long been the subject of debate. To identify any north/south genetic divergence between the Palaearctic and Sino‐Japanese realms proposed by previous studies, we conducted a comparative phylogeographical study involving three passerine species with wide latitudinal distributions in eastern China. Location: Eastern China. Methods: Two mitochondrial genes and three nuclear introns were amplified and sequenced. Population structures were analysed using intra‐specific phylogeny, tcs networks, AMOVA and structure inferences. We tested for evidence of genetic barriers based on pairwise differences. Lineage divergences, demographic dynamics and gene flow between lineages were estimated using Bayesian methods. Results: A congruent north/south phylogeographical divergence was identified for three species. A geographical barrier was inferred at c . 40° N in eastern China. The population sizes of the northern and southern lineages have both been stable through the late Pleistocene, while multiple divergences were inferred during the early and middle Pleistocene. Main conclusions: Our results suggest a general phylogeographical break in north‐eastern China, coinciding with the Palaearctic/Sino‐Japanese boundary. Physical blocking of the Yan Mountains and fragmentation of suitable habitat during glacial stages between the north and south probably acted together to provide long‐lasting barrier effects. Our comparative phylogeographical approach demonstrates that the Palaearctic/Sino‐Japanese boundary may represent a gene‐flow barrier even within widespread species.